Electric injury: a case series - Sharma, Naveen; Khanna, Kunal; Dagar, Tarun; Giri, Sandeep K.; Pal, Vijay; Kumar, Kuldeep; Sharma, Luv (International Journal of Research in Medical Sciences, 2022)
In the modern era, electricity acts as a vital zone for mankind. The most important external sign of electrocution is the electric mark. The internal findings of electrocution are usually unspecific. The electric mark can also be of postmortem origin and is therefore not a reliable proof that the electric shock occurred before death, unless the survival time was long enough for an inflammatory response of the affected tissue. Various cases of electrocution have been reported in literature but as per the best of authors knowledge none of them have been clearly explained for the establishment of complete electric circuit in reported cases; required for fatal electrocution. In the present case series, authors’ report and discuss the three cases of electrocution under different circumstances with deviations in expectations. Because of the diagnostic problems authors also discuss the significance and careful evaluation of incident/death scene in all definitive as well as suspected cases of electrocution and emphasize on various components required for complete electric circuit for flow of current.